Increased Mortality in Elderly Patients with Sarcopenia and Acetabular Fractures. (1st February 2017) - Deren, Matthew E.; Babu, Jacob; Cohen, Eric M.; Machan, Jason; Born, Christopher T.; Hayda, Roman
Abstract : Background: Sarcopenia is a condition of clinically relevant loss of muscle mass and function. Acetabular fractures in elderly patients are common and difficult to treat. This study aimed to determine if sarcopenia is common in elderly patients with acetabular fractures and correlates with lower-energy mechanisms of injury, higher rates of complications, and higher mortality than patients with normal muscle mass. Methods: The Rhode Island Hospital Trauma Database was queried for patients who were ≥60 years of age from 2005 to 2014 using the International Classification of Diseases, Ninth Revision, code for closed acetabular fracture, 808.0. Charts were retrospectively reviewed for demographic data, operative intervention, mechanism of injury, mortality, comorbidities, and other factors. Computed tomography (CT) was used to determine the muscle cross-sectional area and to calculate the skeletal muscle index. Results: The database revealed 192 patients coded for acetabular fracture; of these, 181 were correctly diagnosed. Ninety-nine patients had recorded body mass index (BMI) and adequate CT scans to measure the skeletal muscle index. Forty-two patients (42.4%) had sarcopenia, and 57 patients (57.6%) did not have sarcopenia. There were no significant differences in demographic characteristics between the groups with the exception of BMI and sex. BMI was higher in patients who did not have sarcopenia (31.7 kg/m 2 ) than it was in patients with sarcopenia (23.6 kg/m 2 ) (p < 0.001). Male sex was significantly greater (p = 0.0104) in patients with sarcopenia at 76.2% (32 of 42 patients) than in patients without sarcopenia at 50.9% (29 of 57 patients). Fractures in patients without sarcopenia were associated with a higher-energy mechanism of injury in 78.9% of cases compared with 52.4% of cases of patients with sarcopenia (p = 0.005). Sarcopenia was significantly associated (p = 0.0419) with increased 1-year mortality (28.6%) compared with the absence of sarcopenia (12.3%). This association was even stronger if in-hospital mortality was excluded (p = 0.00074). Finally, anterior column fractures were more likely (p = 0.017) to be sustained by patients with sarcopenia at 47.6% (20 patients) than by patients who did not have sarcopenia at 24.6% (14 patients). Conclusions: Sarcopenia is common in elderly patients with acetabular fractures and is associated with lower-energy mechanisms, anterior column fractures, and higher risk of 1-year mortality. Level of Evidence: PrognosticLevel III . See Instructions for Authors for a complete description of levels of evidence.